It's been a little too long since I've has to do this. Can someone please remind me, how do you get from: ∂u/∂t = C(∂u/∂g) to ∂^2u/∂t^2 = (C^2)(∂^2u/∂t^2) The notation here is a little clumsy, but I'm just taking the second PDE of each side. How does the C^2 get there? Seems like it ought to be C but I can't put my finger on a proof either way. By the way, this comes up in a derivation of the wave equation: ∂^2u/∂x^2 = (1/c^2)(∂^2u/∂t^2) starting from u(x,t) = u(x ± ct) I'm sure someone out there knows this. Thanks for your help.